Lung Ultrasound as a Promising Diagnostic Tool for Primary Graft Dysfunction after Lung Transplantation - Schroeder, Ines; Scharf, Christina; Schneider, Julia; Weggesser, Patricia; Hübner, Lucas; Kneidinger, Nikolaus; Michel, Sebastian; Schneider, Christian; Clevert, Dirk-Andre; Sabel, Bastian; Irlbeck, Michael; Scheiermann, Patrick (Ultraschall in der Medizin - European Journal of Ultrasound, 2023)
Purpose The aim of the study was to evaluate whether the quantification of B-lines via lung ultrasound after lung transplantation is feasible and correlates with the diagnosis of primary graft dysfunction.Methods Following lung transplantation, patients underwent daily lung ultrasound on postoperative days 1–3. B-lines were quantified by an ultrasound score based on the number of single and confluent B-lines per intercostal space, using a four-region protocol. The ultrasound score was correlated with the diagnosis of primary graft dysfunction. Furthermore, correlation analyses and receiver operating characteristics analyses taking into account ultrasound score, chest radiographs, and PaO2/FiO2 ratio were performed.Results A total of 32 patients (91 ultrasound measurements) were included, whereby 10 were diagnosed with primary graft dysfunction. The median B-line score was 5 [IQR: 4, 8]. There was a significant correlation between B-line score and the diagnosis of primary graft dysfunction (r = 0.59, p < 0.001). A significant correlation could also be seen between chest X-rays and primary graft dysfunction (r = 0.34, p = 0.008), but the B-line score showed superiority over chest X-rays with respect to diagnosing primary graft dysfunction in the receiver operating characteristics curves with an area under the curve value of 0.921 versus 0.708. There was a significant negative correlation between B-line score and PaO2/FiO2 ratio (r = –0.41, p < 0.001), but not between chest X-rays and PaO2/FiO2 ratio (r = –0.14, p = 0.279).Conclusion The appearance of B-lines correlated well with primary graft dysfunction and outperformed chest radiographs.
Keywords: Chest; Point of care; Lung Ultrasound; B-lines; Primary Graft Dysfunction